ҚАРАҚАЛПАҚ ХАЛЫҚ ЕРТЕКЛЕРИНДЕГИ ЛИНГВОМӘДЕНИЙ ТҮСИНИКЛЕРДИӉ МЕТАФОРИЗАЦИЯСЫ - Кунназарова, Ш.М. (SCIENCE and SOCIETY, 2021)
The article analyzes the metaphors of the Karakalpak folk tales in the linguocultural analysis. The role of metaphors in the Karakalpak folk tales is demonstrated by examples that this process is unique not only for the Karakalpak people, but also for many peoples of the world.
Keywords: linguoculturology; tradition; metaphor; cultural connotation; national and cultural values